E-commerce improves dietary quality of rural households in China - Jiexi Shen; Zhanguo Zhu; Matin Qaim; Shenggen Fan; Xu Tian (University of Bonn, Center for Development Research (ZEF), 2023)
E-commerce is gaining importance in the food sector of many countries, and its potential influence on people's access to food and dietary choices is yet to be thoroughly investigated. In this study, we analyze data from a food consumption survey conducted in rural China in 2021 to examine the impact of e-commerce on individual food consumption patterns and dietary quality. Our results with instrumental variable models show that e-commerce significantly reduces the consumption of staple foods, such as cereals and potatoes, while it increases the consumption of legumes, nuts, milk, and milk products, even after controlling for income and other confounding factors. Additionally, e-commerce contributes to higher dietary diversity and dietary quality among rural households. In the face of shrinking physical markets in rural areas, it seems that rural e-commerce can serve as an important mechanism to improve food access and meet the diversifying dietary demands of rural residents.
Keywords: D12; I15; O33; Q13; 330; e-commerce; dietary patterns; dietary quality